2014
DOI: 10.1097/hjh.0000000000000149
|View full text |Cite
|
Sign up to set email alerts
|

Leptin induces cardiac fibrosis through galectin-3, mTOR and oxidative stress

Abstract: The data suggest that leptin locally produced in the heart could participate in the fibrosis observed in HFD by affecting collagen turnover. Collagen synthesis induced by leptin seems to be mediated by the production of galectin-3, TGF-β and CTGF through oxidative stress increased by activation of mTOR pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
77
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 64 publications
13
77
1
Order By: Relevance
“…In this study, MA from HFD show augmented content of type I collagen, which comprises 60% of the vascular wall collagens 51 , without changes in type III collagen. Similar findings have been described in conduit arteries from a Wistar rat DIO model 52 .…”
Section: Discussionsupporting
confidence: 76%
“…In this study, MA from HFD show augmented content of type I collagen, which comprises 60% of the vascular wall collagens 51 , without changes in type III collagen. Similar findings have been described in conduit arteries from a Wistar rat DIO model 52 .…”
Section: Discussionsupporting
confidence: 76%
“…Galectin-3 inhibition by N-acetylglucosamine reduced leptin-induced collagen I secretion in cardiac fibroblasts, suggesting that the increase in leptin during obesity can lead to cardiac fibrosis, which can be partially inhibited by limiting galectin-3 activity. 48 Similar results were found in an aldosterone-induced vascular fibrosis animal model demonstrating that aldosterone-induced vascular fibrosis was characterized by increased galectin-3 and collagen I expression in vascular smooth muscle cells and aorta. This form of vascular fibrosis was suppressed in galectin-3 knockout mice or mice treated with citrus pectin, a galectin-3 inhibitor.…”
supporting
confidence: 71%
“…The molecular mechanisms responsible for the mTOR‐dependent activation of NOX and NF‐κB in response to BCAA are unknown and this is a limitation of our study. However, other authors have also found a role for mTOR in oxidative stress generation40, 41 or NF‐κB activation in response to different stimuli or pathological conditions 42, 43. Besides mTORC1, BCAA trigger several signalling responses via the activation of AMPK, which plays a role in cellular energy homoeostasis.…”
Section: Discussionmentioning
confidence: 99%